Does biomass fuel use for cooking affect early childhood development? A case study of Kiribati - Ashar Awan; Dil B. Rahut (Asian Development Bank Institute (ADBI), 2023)
Early childhood development (ECD) sets the starting point for future health, learning, and wellbeing; hence the United Nations Sustainable Development Goals recognize the importance of ECD in the global agenda. Therefore, we present evidence of the possible influence of prolonged biomass use for cooking on ECD at the household level using data from MICS 2018-19 for Kiribati in the Pacific islands. These findings have important policy implications for promoting ECD in the Pacific region, particularly for Kiribati, where the use of biomass for cooking is prevalent. The study recommends scaling up the use of clean cooking fuels to improve the health and well-being of young children in the region.
Keywords: Q40; R20; P46; 330; biomass use for cooking; clean cooking fuels; early childhood development; Kiribati